Switching to ocrelizumab in RRMS patients at risk of PML previously treated with extended interval dosing of natalizumab. (April 2021) - Mancinelli, Chiara Rosa; Scarpazza, Cristina; Cordioli, Cinzia; De Rossi, Nicola; Rasia, Sarah; Turrini, Maria Vittoria; Capra, Ruggero
Discontinuation of natalizumab in patients with relapsing-remitting multiple sclerosis (RRMS) at risk of progressive multifocal leukoencephalopathy (PML) is associated with disease reactivation. Forty-two RRMS patients, who switched from an extended interval dose (EID) of natalizumab to ocrelizumab, underwent magnetic resonance imaging (MRI) and clinical monitoring during washout and after ocrelizumab starting. During the first 3 months, disease reactivation was observed in five (12%) patients; 6 months after ocrelizumab starting, no further relapses were recorded, and Expanded Disability Status Scale (EDSS) remained stable in 38 (90%) patients. In conclusion, ocrelizumab could be considered a choice to mitigate the risk of disease reactivation in patients previously treated with natalizumab-EID.